Furthering justice or promoting impunity? A critical analysis of the propesed criminal jurisdiction in the African court of justice and human rights - Akonumbo, Atangcho Nji (University of Pretoria, 2011)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2010.